A typology for the classification, description and valuation of ecosystem functions, goods and services - De Groot, R.S.; Wilson, M.A.; Boumans, R.M.J.
An increasing amount of information is being collected on the ecological and socio-economic value of goods and services provided by natural and semi-natural ecosystems. However, much of this information appears scattered throughout a disciplinary academic literature, unpublished government agency reports, and across the World Wide Web. In addition, data on ecosystem goods and services often appears at incompatible scales of analysis and is classified differently by different authors. In order to make comparative ecological economic analysis possible, a standardized framework for the comprehensive assessment of ecosystem functions, goods and services is needed. In response to this challenge, this paper presents a conceptual framework and typology for describing, classifying and valuing ecosystem functions, goods and services in a clear and consistent manner. In the following analysis, a classification is given for the fullest possible range of 23 ecosystem functions that provide a much larger number of goods and services. In the second part of the paper, a checklist and matrix is provided, linking these ecosystem functions to the main ecological, socio-cultural and economic valuation methods.
Keywords: CLASSIFICATION OF ECOSYSTEM FUNCTIONS; TYPOLOGY OF GOODS AND SERVICES; ECOLOGICAL AND SOCIO-ECONOMIC VALUATION